Folate deficiency among Filipino pregnant women, 6th National Nutrition Survey (2006)
Folate deficiency is considered an important risk factor for neural tube defects (NTD), spontaneous abortion, intrauterine growth retardation and preterm births. Folate deficiency may also result to macrocytic type of anemia which is a common late finding in pregnancy. Taking into account the health danger resulting from folate insufficiency, there is a need to investigate folate status of pregnant women in a nationwide scale. The objectives of the study were to determine the prevalence of folate deficiency of Filipino pregnant women included in the 6th National Nutrition Survey (NNS), and determine the association of supplement use, age of the subjects, age of gestation, level of education, prenatal care, past occurrence of birth defects, history of miscarriages and some lifestyle factors such as alcohol consumption, cigarette use and taking of oral contraceptive pills prior to pregnancy with folate status. A total of 584 pregnant women with complete data on folate parameters were included in the study. Blood samples were collected in a non-fasted state. Red blood cell (RBC) and serum folate were analyzed using radioimmunoassay (RIA). The study also made use of interviews to gather gynecological related data such as age, gravida, parity and other health-related information. Subclinical folate deficiency was identified by the following criteria: RBC and serum folate level lower than 175 ng/ml, and 3.0 ng/ml, respectively. The results of the study showed that with serum folate as indicator, more than half of 51.7% (95% Cl = 46.9-56.7) of the pregnant women had serum folate level less than 3 ng/ml. Prevalences of low serum folate was 39.9% in the 1st trimester, 54.3% in the 2nd and 53.6% in the 3rd trimesters. Based on red cell folate, 37.5% (95% Cl = 33.2-41.8) of the 584 subjects had depleted folate stores. By stage of pregnancy, the highest prevalence of depleted folate stores occured among pregnant women in the 1st trimester (47.7%) than in the 2nd (36.3%) and 3rd trimester (35.0%) suggesting that a significant number of pregnant women had insufficient folate stores before pregnancy. A separate evaluation of the dietary adequacies on the same pregnant subjects done by the Food Consumption Survey showed that except for niacin, energy and all other nutrients fell below the respective Recommended Energy and Nutrient Intake (RENI). Use of supplements before and during pregnancy reduced the risk of folate deficiency. Pregnant women who smoked, on the other hand , had 3-fold increased risk to folate deficiency compared to the non-smokers. There was a non-significant trend of lower prevalences of folate deficiency among women who sought prenatal visits than those who did not. Conclusion and Recommendations: The high percentages of subnormal values of serum and red cell folate indicate an alarmingly high prevalence of folate deficiencies. The findings strongly suggest that public health campaign is needed to promote the consumption of folate rich food and use of folic acid supplements among all women of reproductive age. Pregnant women should be asked to stop smoking. If she has difficulty to do so, she should take higher doses of folic acid periconceptionally. Lastly, the routine prenatal care visits to doctor or health centers would be an ideal opportunity to counsel pregnant women to take folic supplements.